2018
DOI: 10.1186/s12887-018-1022-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention-deficit/hyperactivity disorder symptoms and their associations with sleep schedules and sleep-related problems among preschoolers in mainland China

Abstract: BackgroundAttention-deficit/hyperactivity disorder (ADHD) among children is an increasing public health concern. The identification of behavioral risk factors, including sleep quality, has important public health implications for prioritizing behavioral intervention strategies for ADHD. Herein, this study aimed to investigate the prevalence of high levels of ADHD symptoms and to explore the association between sleep schedules, sleep-related problems and ADHD symptoms among preschoolers aged 3 to 6 years in mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
0
11
1
1
Order By: Relevance
“…This could be due to the fact that Conners ECGI includes not only items about restlessness-impulsivity but also emotional lability, which may be more observable or higher in girls. There was a notably high rate of symptoms in the clinical range (Conners T ≥ 70) reported by parents in both pre-school (26.2%) and school-age children (34%, reaching a value of 42% in boys), which is clearly higher than the rates reported by other authors (Aboul-ata & Amin, 2018; Canals et al, 2018; Cao et al, 2018; Cerrillo-Urbina et al, 2018; Joshi & Angolkar, 2018; Yadegari et al, 2018). Although the high rate of symptoms detected in boys will be related to the high prevalence of ADHD in males (4% in pre-schoolers and 11.9% in school-age children), it could also be due to the characteristics of the screening test used to assess the risk symptoms (Conners ECGI and Conners 3 ADHD Index).…”
Section: Discussioncontrasting
confidence: 56%
“…This could be due to the fact that Conners ECGI includes not only items about restlessness-impulsivity but also emotional lability, which may be more observable or higher in girls. There was a notably high rate of symptoms in the clinical range (Conners T ≥ 70) reported by parents in both pre-school (26.2%) and school-age children (34%, reaching a value of 42% in boys), which is clearly higher than the rates reported by other authors (Aboul-ata & Amin, 2018; Canals et al, 2018; Cao et al, 2018; Cerrillo-Urbina et al, 2018; Joshi & Angolkar, 2018; Yadegari et al, 2018). Although the high rate of symptoms detected in boys will be related to the high prevalence of ADHD in males (4% in pre-schoolers and 11.9% in school-age children), it could also be due to the characteristics of the screening test used to assess the risk symptoms (Conners ECGI and Conners 3 ADHD Index).…”
Section: Discussioncontrasting
confidence: 56%
“…A systematic review of 30 short-and longterm studies underlined the clinical benefits of physical exercise in behavioral and cognitive deficits in children with ADHD (Ng et al, 2017). Regarding sleep schedules, a study by Cao et al (2018), with a sample of 15,291 preschool children in China, showed that delayed sleep time was closely associated with the risk of developing ADHD symptoms, while longer sleep times (> 8.5 hours) were associated with a reduced risk of developing ADHD symptoms. When it comes to using electronic media, children with ADHD can be particularly vulnerable to overuse.…”
Section: Alternative Types Of Interventionmentioning
confidence: 99%
“…17 The C-ASQ is derived from the Revised Conners Parent Rating Scale and has been translated and validated for use in Chinese population. 18…”
Section: Adhd Symptomsmentioning
confidence: 99%